An insight of sustainable transportation: a study in Klang Valley / Ho Khay Siang and Nadzirah Zainordin - Ho, Khay Siang; Zainordin, Nadzirah (2018)
The quality of transportation service is the main factor to increase the level of economic and social. By increasing the system may buzz-up all sectors and may contribute the benefit to the community. This research was conducted in Klang Valley. The reason in choosing this location is because of the role that the location plays in contributing to the economic sector in Selangor state itself. The methodology used to conduct this research was a quantitative method; 200 set of questionnaire were distributed to get the perception on the concept of sustainable transportation among respondents. The questionnaire was distributed to those who have knowledge towards sustainable transportation and it was limited to those who have experience in construction sector only. The objectives of this research were to investigate the construction player's perception towards sustainability transportation in Klang Valley and to identify the barriers factor in implementing this concept. It is hoped that this research able to create awareness on implementing this concept because of its beneficial to the routine activities as well as can generate and increase awareness to the public.